2016
DOI: 10.1155/2016/1876901
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia due to Primary Hepatic Lymphoma

Abstract: A 65-year-old female with a history of mixed connective tissue disease and pulmonary fibrosis on azathioprine, hydroxychloroquine, and prednisone (osteoporosis on teriparatide) presented with a 1-month history of hypercalcemia. After discontinuation of teriparatide, the patient's hypercalcemia persisted. Further evaluation revealed primary hepatic lymphoma as the source of her hypercalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A review by Vallet et al [ 23 ] demonstrated that hypercalcemia was independently associated with poor PFS and OS[ 23 ]. Many researchers have reported that 40% of PHL patients have serum calcium abnormality[ 24 , 25 ], but there were only 6 patients diagnosed with hypercalcemia in our study; hence, more data are needed to elucidate its significance in the PHL setting.…”
Section: Discussionmentioning
confidence: 74%
“…A review by Vallet et al [ 23 ] demonstrated that hypercalcemia was independently associated with poor PFS and OS[ 23 ]. Many researchers have reported that 40% of PHL patients have serum calcium abnormality[ 24 , 25 ], but there were only 6 patients diagnosed with hypercalcemia in our study; hence, more data are needed to elucidate its significance in the PHL setting.…”
Section: Discussionmentioning
confidence: 74%
“…Full blood counts are usually within the normal range unless the bone marrow or spleen is involved ( 38 ). Other occasional laboratory findings include monoclonal paraproteinemia and hypercalcemia, which is possibly the result of the secretion of calcitriol by lymphoma cells ( 39 , 40 ).…”
Section: Primary Hepatic Lymphomamentioning
confidence: 99%